Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, Dana Alokasi Khusus dan Dana Bagi Hasil terhadap Belanja Modal - Mutiara, Asti; Astuti, Yanti Puji (JABKO: Jurnal Akuntansi dan Bisnis Kontemporer, 2020)
This study aims to determine the effect of local revenue, general allocation funds, special allocation funds, and revenue sharing funds on capital expenditure in the District / City Governments in Central Java in 2015 - 2019. The population used in this study is to use the Regional Government APBD Report Regencies / Cities in Central Java in 2015-2019. The sample used in this study is to use the Saturation Sampling Technique which consists of 29 Regencies and 6 Cities. The data used in the form of secondary data on district / city APBD budget reports in Central Java. This research uses multiple linear regression analysis method with SPSS 23 program. The results showed that the original regional income, general allocation funds, special allocation funds, and revenue sharing funds simultaneously affected capital expenditure with a significant value of 0,000. Regional original income has an effect on capital expenditure with a significant value of 0,000, general allocation funds have an effect on capital expenditure with a significant value of 0,000, special allocation funds have no effect on capital expenditure with a significant value of 0.46 and revenue sharing funds have an effect on capital expenditure with a significant value of 0,000 .